Pendekatan Fenomenologi Dalam Komunikasi Antaragama - Y, Yuangga Kurnia (AL-ADYAN, 2018)
This paper will research the phenomenological approach in interfaith communication. The great development of communication media in this global era remains a classic problem of communication, that is an interfaith and interreligion communication. The strength globalization’s flow which is destroying every borders between nations, regions and cultures, unfortunately, is not strong enough to destroy one solid wall, the border of religion and faith’s differences. That problem becomes bigger and more complicated when the borders of religions and faiths create an unhealthy and unsmooth communication among people, as individual or communal. A lot of religious sentiments and communal violences based on religious view’s differences and misunderstanding among faiths – which is happen from centuries ago - take place for the umpteenth time in many cities in Indonesia dan many countries in another hemisphere. Phenomenological approach is a theoretical perspective based on concept “back to the things themselves”. In other words, this study is a structural consciousness that allows those consciousness to discover and understanding the objects outside of it. In Husserl’s phenomenology, he made an epoche and eidetic vision as starting point of this perspective. Both of that concepts are a main and basic concept which is needed in interfaith communication to postponing judgement and looking with their own believer’s perspective. This approach is radically needed to smooth out the interfaith communication. This approach also allows the transcultural communication and identity transformation from one religion’s followers to another to reach a mutual agreement and decrease religious sentiments which are born from subjectivity of one religion’s followers in judging another religions and their followers.Keywords: Phenomenology, epoche, interfaith communication, cross-cultural                   communication